Triumph of the commons : Wikia and the commercialization of open-source communities in 2009 - Greenstein, Shane M.; Frazzano, Rebecca; Meagher, Evan (London : SAGE Publications Ltd, 2017)
In 2009 Wikia was the Internets largest for-profit provider of hosted open-source wikis, with over a million daily users. After five years of existence, the organization had supported a wide range of exploratory activities, experiencing both success and failure. With approximately $3 million of cash on hand, Wikia turned cash flow positive in 2009, with revenues of approximately $4.5 million, affording it time and flexibility to try new things. Some of the companys employees and investors suggested that Wikia should attempt to expand and market itself more aggressively, but which strategic direction should receive priority? The case presents many of the issues and tradeoffs facing CEO Gil Penchina as he formulates these priorities.
Originally published: Greenstein, S., Frazzano, R., & Meagher, E. (2009). Triumph of the Commons: Wikia and the Commercialization of Open-Source Communities in 2009. 5-309-509. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Wikia -- Case studies; Open source software -- Case studies; Information services -- Case studies; Internet industry -- Case studies